Brand Registration as a Marketing Strategy and Customer Loyalty of Natural Color Batik in Kampung Alam Malon Village - Santoso, Budi; Pratomo, Inge Widya Pangestika; Hidayah, Nida Nur; Banna, Sabri; Kusumaningtyas, Rindia Fanny (Indonesian Journal of Advocacy and Legal Services, 2019)
rand is a name, symbol, mark, design or combined of them for use as an individual identity, organization or corporations on goods and services possessed of discernment with the other service. Globally, the right brands Brand will be used as strategy to market products or services,Considering the registration brand will need as an id to distinguish the results of the production of produced a person or some people in together or legal entity with the production of another person or another law office. The writer applied law and sociologicalapproach to study these issues so that the brand registration is importat to marketing product and customer loyality Batik of Malon Nature Village.